Preparation of carrier-free phosphorus-32 - Aleta, Carlito R. (1965)
Two methods of preparing carrier-free P-32 from irradiated sulfur were studied in an attempt to gain information about the future P-32 production by PARC (Philippine Atomic Research Center). One method is solid-liquid extraction using water as solvent and 2-octanol as wetting-agent; the other is liquid-liquid extraction using a mixture of glacial acetic acid and acetic anhydride (3:1 by volume) as solvent.
Economy, both in time and in chemicals used, is a dominant feature of the water-octanol procedure, while the higher percentage of extraction is the advantage of the other process.
In this study, emphasis was laid upon the determination of process efficiency and the purity of the product, and upon the identification of phosphorus-32 and the chemical forms of phosphorus.
Thesis (M. Engineering)--University of the Philippines, Diliman.
Keywords: Phosphorus